Myeloidderived suppressor cells: Escorts at the maternal–fetal interface - Pang, Bo; Hu, Cong; Li, Huimin; Nie, Xinyu; Wang, Keqi; Zhou, Chen; Yi, Huanfa (Frontiers in Immunology, 2023)
Myeloid-derived suppressor cells (MDSCs) are a novel heterogenous group of immunosuppressive cells derived from myeloid progenitors. Their role is well known in tumors and autoimmune diseases. In recent years, the role and function of MDSCs during reproduction have attracted increasing attention. Improving the understanding of their strong association with recurrent implantation failure, pathological pregnancy, and neonatal health has become a focus area in research. In this review, we focus on the interaction between MDSCs and other cell types (immune and non-immune cells) from embryo implantation to postpartum. Furthermore, we discuss the molecular mechanisms that could facilitate the therapeutic targeting of MDSCs. Therefore, this review intends to encourage further research in the field of maternal–fetal interface immunity in order to identify probable pathways driving the accumulation of MDSCs and to effectively target their ability to promote embryo implantation, reduce pathological pregnancy, and increase neonatal health.